Metabolome and transcriptome reveal dynamic patterns of floral scent release and gene expression during flower development in carnation - Luhong Leng; Rui Huang; Zhiqiang Wu; Xiaoni Zhang (Horticulture Advances)
Abstract Carnations (Dianthus spp.), among the most significant ornamental flowers globally, are widely appreciated for their aesthetic appeal. Floral scent, a key quality attribute, leaves a lasting impression on consumers. However, the release patterns and regulatory mechanisms of the major scent components in contemporary carnation cultivars remain poorly understood. Gas Chromatography-Mass Spectrometry (GC–MS) and RNA sequencing identified 14 volatile organic compounds (VOCs) as the primary aromatic constituents in the fragrant ‘Scarlet Queen’. Notably, eugenol, β-caryophyllene, and cis-3-hexenyl benzoate are the principal contributors. VOC emission in ‘Scarlet Queen’ predominantly occurs at the full bloom (S6) and early senescence (S7) stages. Additionally, this study elucidated the metabolic pathways of key aroma compounds and pinpointed crucial genes involved in their biosynthesis, including phenylalanine ammonia-lyase (PAL), coniferyl alcohol acyltransferase (CFAT), and two eugenol synthase (EGS) genes for eugenol, as well as isopentenyl diphosphate isomerase (IDI) and terpene synthase (TPS) genes for β-caryophyllene. Furthermore, the expression patterns of DcaMYB78, DcaMYB84, and DcaMYB90 correlated with the eugenol release profile, as confirmed by k-means clustering and co-expression network analysis. This study not only delineates the principal aromatic compounds and their biosynthetic pathways in carnations but also provides a vital framework for improving the scent quality of cut carnations.